KOMPARASI PENGGUNAAN MEDIA GOOGLE EARTH DENGAN PETA DIGITAL PADA MATERI PERSEBARAN FAUNA KELAS XI IPS DI SMA NEGERI 1 SEMARANG - Nur Isnaini (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2015)
Madrasah Aliyah Negeri 1 Semarang is one of Madrasah Aliyah which has sufficient facilities. However, thelearning process of the school implies y simple learning media. Ideally, along with technology development,geography learning is supposed to utilize the technology and facilities maximally. The purpose of this research isto know the implementation of Google earth media and map digital, and to know the comparison of learningoutcome using Google earth media and using digital map media of fauna distribution. Subject of this research isIPS students in grade XI of MAN 1 Semarang. Experiment group (learning using Google Earth media) is IPS 2students in grade XI while IPS 3 students in grade XI become controller group (learning using digital map). Thisresearch is quasi experimental design. Variable of this research is learning outcome of the student with animaldistribution material using Google earth media, and learning outcome of the students using digital map media offauna distribution. Method of collecting data used documentation, questioner, and test. Analysis of the researchshows thitung ttabel. It means that hypothesis is approved. Therefore, I can conclude that geography learningoutcome on distribution fauna material using Google Earth media is better than using digital map media ofdistribution fauna.